Setting up an obesity clinic – The SMART approach - Kapoor, Nitin; Arora, Saurabh; Kalra, Sanjay (Journal of the Pakistan Medical Association, 2023)
Management of obesity is often complex and requires a multidisciplinary team approach. There is an emerging need for establishing more dedicated bariatric clinics in the south Asian region. These clinics help to provide an individualized patient centric management through different specialists involved in obesity therapy under one roof. Furthermore, these clinics help to facilitate obesity management like any other chronic disease which requires long term follow-up. This article details the essential components required in setting up an obesity clinic in the south Asian region. The SMART approach (S-Setting; MManagement team; A-Algorithmic approach; R-Research and referral; T-Technology) is an easy to grasp summary of the essential components required for setting a bariatric clinic. Keywords: Bariatric clinic, Obesity clinic, Multidisciplinary approach, Obesity management, Barocrinology